Pengaruh Strategi Marketing Public Relations terhadap Minat Pasien Imunisasi Home Care pada Klinik Imuni Surabaya - Meilinda Laurensia Febrihianto (Syntax Corporation Indonesia, 2024)
The aim of this study is to find out whether the impact of Marketing Public Relations strategies, i.e. pull, push and pass strategy partially and simultaneously on the interest of home care immunization patients at Klinik Imuni Surabaya. This research is a type of quantitative descriptive study with an instrument in the form of a questionnaire that has undergone validity and reliability testing. The test methods used are classical assumption tests, double linear regression tests, and hypothesis tests using t-test and f-test. The results of this study show that there is a significant positive impact of pull, push and pass strategy partially on the interest of home care immunization patients at Klinik Imuni Surabaya and there is also a high and significant impect of pull, push, and pass strategies simultaneously on the interest of home care immunization patients at Klinik Imuni Surabaya. This means that the better the three forms of Marketing Public Relations (MPR) strategies, consisting of pull, push, and pass strategies are applied either separately or together, the higher interest of patients in utilizing home care immunization services at Klinik Imuni Surabaya.